ANALISIS KEEKONOMIAN METODE PRODUKSI SEKALIGUS DAN PRODUKSI BERTAHAP PADA RESERVOIR SOLUTION GAS DRIVE - Surianto Sinurat, Andi
Reservoir pressure of a solution gas drive reservoir will deplete quickly as the production start. This depletion drives quick declining of production rate too. Therefore, we need an appropriate production strategy to accomplish optimum production. The reservoir model in this thesis has three layers to be treated. This study will give comparison of recovery factor obtained between staged production (different time in extracting fluid from each layer) and extract fluid from three layers at the same time. The production constraint used in this stimulation stated is minimum oil production rate 30 stb/d. Peak and plateau production strategy are applied on both of these methodes. Peak production strategy applied by generating rate production around 60% and 70% from absolute open flow to obtain maximum oil recovery. Plateau production strategy determined by generating lower production rate to hold decline rate and smaller size of production facilities. On this simulated reservoir, peak production strategy gives higher recovery factor. The field development economy varies and depends on capital investment, revenue, and production time. Indicators economy applied in this thesis are net present value, internal rate of return, and pay out time. All these aspects used to determine the best methode in developing this field. Method of production which gives higher profit in this thesis obtained by using staged production through peak production strategy.